Maria Montessori’s Philosophy of Early Childhood Education and its Implications for Nigerian Education - Oyelade, A. F. (NIU Journal of Humanities; Vol 3 No 1 (2018): KIU Journal of Humanities, Vol. 3 No. 1, March 2018, 2018)
This study is on Maria Montessori’s philosophy of early childhood education and its implications for Nigerian education. Maria Montessori’s thoughts, statements, and actions on early childhood education constitute her philosophy of early childhood education. It is important to study her philosophy of early childhood education because it has assumed popularity at various times in various parts of the world, including: Italy, Britain, and United States of America. It has also gained some recognition in Nigerian early childhood education. However certain details of her philosophy of early childhood education do not follow conventional process of early childhood education, although the process of education brings about speedy learning. It is therefore important to analyse her philosophy of early childhood education and its implications for Nigerian education. The research method employed in the study is the method of philosophical analysis. The philosophical analysis employed includes: logical, linguistic, expository, and critical analyses. It was found that Maria Montessori’s philosophy of early childhood education lays emphasis on recognition of the stages of development of children, enabling learning environment, individualised teaching, child-centred education, and on teacher’s knowledge of child psychology. The education promotes personal development of children speedily, and societal development. It was found that Nigerian early childhood education indicates recognition of Montessori’s philosophy of early childhood education. The implications of her philosophy of education for Nigerian education therefore, are that the education should continue to feature in Nigerian early childhood education. It is therefore recommended that Nigeria pursues Maria Montessori’s education with greater intensity. Key words: Maria Montessori, philosophy of education, early childhood education, philosophical analysis, Nigeria.